Studying the Lived Experiences of a Volunteer Fighter from the Iran-Iraq War, 1980-1988 (The Sample of Study: Viva Teer Comail Written By Mohsen Motlaq) - fariba nazaripourkiyaei; alireza ghobadi; Farah Torkaman (توسعه اجتماعی)
War is a socio-cultural phenomenon when after bullets came and went in the war the various incidents happening should be noted because they are full of the signs and meaning. So finding the meaning of it is very necessary. One way to find out how these events unfold is to look at the lived experiences of war soldiers which are narrated in the form of memoirs of this phenomenon. Literal texts which have been created in this case are one the most important references for showing and interpreting such event. For this purpose we refer to the literal productions in which the lived experience of a volunteer activist participating in the Iran-Iraq war is recorded and documented in a work called “Long lived Kamil” with his written narration. In this study, we used Clifford Girtz's interpretive theory and chose the type of qualitative studies to capture the concepts. Using the method and technique of qualitative content analysis, we classified the information and finalized the interpretation. The results of this study show that war is not just a battle of bullets, but Rather, the lived experiences of the actor on the battlefield is full of emotions and meanings that are created and displayed in accordance with the time and place of his life event which we will become more familiar with in the main text of article.